La diffusion de la géographie théorique et quantitative européenne francophone d’après les réseaux de communications aux colloques européens (1978-2011) - Sylvain Cuyala (Cybergeo, 2013)
This work is part of a research on European French-speaking TQG’s diffusion and development. A three stages development of this scientific movement (emergence, assertion and diversification)is tested through the study of a specific event: European colloquiums of Theoretical and Quantitative Geography. Two sets of data are used: the lists of communications and a set of fifty-five interviews of French-speaking European actors. We first analyze the quantitative evolution of communications from 1978 to 2011 and then the social networks corresponding to the authors, with a focus on their geographical settings. In the light of this formalization, the movement appears to develop from intra-laboratory collaborations to the emergence of cross-site and international cooperation.